Oil and the macroeconomy in a changing world: A conference summary - Christopher L. Foote; Jane S. Little (Federal Reserve Bank of Boston, 2011)
Analysis of oil-price movements is once again an important feature of economic policy discussions. To provide some background for this analysis, this paper summarizes a conference on the oil market held at the Federal Reserve Bank of Boston in June 2010. Four cross-cutting themes emerged from this symposium, which included scientific experts, market participants, business leaders, academics, and policymakers. First, the decline in real oil prices that followed the 1970s' oil shocks is unlikely to be repeated today, because there are fewer ways in which oil-importing countries can reduce oil demand or expand domestic supplies in response to higher prices. The second lesson of the conference, however, is that any prediction about oil markets is highly uncertain, a fact illustrated by the wide confidence intervals that result when futures-market data are used to quantify forecast uncertainty. Third, there is little consensus on whether new financial investment in commodity index funds has increased the volatility of oil prices. Finally, changes in oil prices still have large effects on the economy. Some research suggests that the rapid run-up in oil prices in 2007-08 may have significantly weakened the U.S. economy in the early stages of the Great Recession.
Keywords: L71; Q4; Q5; 330; Ölpreis; Volatilität; Mineralölmarkt; Makroökonomischer Einfluss; USA